2016
DOI: 10.1021/acs.organomet.6b00482
|View full text |Cite
|
Sign up to set email alerts
|

Basic Reactivity Pattern of a Cyclic Disilylated Germylene

Abstract: In order to estimate the reactivity of disilylated germylene phosphine adducts, a cyclic version of this compound class was reacted with a number of different reagents. Reactions with the chalcogens sulfur, selenium, and tellurium led to dimers of the heavy ketone analogues. Reactions with water and ethyl bromide proceeded to give the respective oxidized germanol and germyl bromide. Two different reactions with alkynes were observed which led either to a germacyclopropene, by addition of tolane to the germylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 75 publications
(180 reference statements)
0
21
0
Order By: Relevance
“…More recently, we reported that reactions of 2 a and related cyclic compounds with tolane form germacyclopropenes . Conversely, the reaction of 2 a with phenylacetylene gives vinylgermylene 10 a , the product of a regio‐ and stereoselective insertion into a Ge−Si bond (Scheme ) …”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…More recently, we reported that reactions of 2 a and related cyclic compounds with tolane form germacyclopropenes . Conversely, the reaction of 2 a with phenylacetylene gives vinylgermylene 10 a , the product of a regio‐ and stereoselective insertion into a Ge−Si bond (Scheme ) …”
Section: Resultsmentioning
confidence: 98%
“…Based on initial studies with cyclic disilylated stannylenes and plumbylenes, our work included PEt 3 and PMe 3 adducts of some cyclic disilylated germylenes and the recent synthesis of PMe 3 and NHC adducts of bis[tris(trimethylsilyl)silyl]germylene …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This PA value is comparable to that for methylamine bases . Therefore, it appears that germylene derivatives can also achieve much higher basicity with suitable substituents, although the PA value of germylene is lower than its lower homologue (carbene and silylene) owing to the reluctance of donation of lone‐pair electron . To augment the basicity of Ge II , isopropyl groups were introduced into system 4 and the calculated PA was found to be 225.0 kcal mol −1 (Table ).…”
Section: Resultsmentioning
confidence: 90%
“…[70] Therefore, it appears that germylene derivatives can also achieve much higherb asicity with suitable substituents, although the PA value of germylene is lower than its lower homologue (carbene and silylene) owing to the reluctance of donation of lone-pair electron. [71] To augment the basicity of Ge II ,i sopropyl groupsw ere introduced into system 4 and the calculated PA was found to be 225.0 kcal mol À1 ( Table 2). These results suggest that bettere lectron-donating groups can improvet he basicity of Ge II .H owever,t hese simple Ge II compounds have not formally achieved superbasicity (PA > 240 kcal mol À1 ).…”
Section: Resultsmentioning
confidence: 99%